Surface modification of a Ti–6Al–4V alloy by thermal oxidation - Guleryuz, H.; Cimenoglu, H.; Çimenoğlu, Hüseyin (Elsevier BV, 2005)
Abstract In this study, the effect of thermal oxidation on the dry sliding wear resistance of a Ti–6Al–4V alloy has been examined. Oxidation has introduced hard surface layers composed of TiO2 and oxygen diffusion zone beneath it. Hardness survey conducted under a load of 10 g with a Vickers pyramid indenter revealed that surface hardness increased from 450 to 1300 HV0,01 upon oxidation at 600 °C for 60 h, which was accompanied by significant improvement in wear resistance. Thus, the dry sliding wear rate of thermally oxidised Ti–6Al–4V alloy was almost negligible when compared to the as-received condition.